Strengthening of Learning Motivation to Bullying Victims by Using Family and School Character Based - Moh Fatkur Rohman (STAI Miftahul Ula Nganjuk, 2019)
The rising of bullying phenomenon in education, especially in Indonesia, shows that bullying is still a severe problem in education. Bullying seems not to have preventive measures effectively and efficiently. In a psychological perspective, bullying behavior can affect various negative impacts for victims experienced, such as decreased learning motivation, an act of revenge against the bullying perpetrators, and loss of victim's confidence and learning interest so that the learning process at school is disrupted. Therefore, in this study, researchers tried to analyze bullying behavior by using several theoretical perspectives. As a result, conceptually, a critical analysis of bullying can be found, and a character-based approach is applied to foster confidence and learning motivation in bullying victims.